1985
DOI: 10.1080/03670244.1985.9990870
|View full text |Cite
|
Sign up to set email alerts
|

The Bulacan nutrition and health study: Part 1. Baseline socioeconomic and related characteristics of subject families and their impact on the nutritional health of infants

Abstract: Using weight for age as the nutritional index, 544 infants were studied longitudinally for health/nutrition status from age 2 months to 26-29 months. Socioeconomic and related data, enumerated on subject families at the start of the study, were used in statistical modelling exercises to develop predictions of their impact on the nutritional health of the subjects. Factors of importance were parent educational attainment, income, family size and early post-natal weight/height characteristics of the subjects the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 3 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…In addition to the implementation of policies to increase the level of formal education among women, IYCF education programs should be targeted toward women with little formal education, because higher maternal nutrition knowledge has been demonstrated to partially compensate for low education in some contexts (39,49). Although it was not evident from our middle-income study setting, it should be noted that the beneficial influence of maternal knowledge or formal education on child growth is understood to be dependent on a minimum level of access to resources (39,(50)(51)(52)(53). Nonetheless, our findings support the growing interest in increasing maternal educational attainment as a potential intervention toward improving child health outcomes (18,(54)(55)(56).…”
Section: Discussionmentioning
confidence: 92%
“…In addition to the implementation of policies to increase the level of formal education among women, IYCF education programs should be targeted toward women with little formal education, because higher maternal nutrition knowledge has been demonstrated to partially compensate for low education in some contexts (39,49). Although it was not evident from our middle-income study setting, it should be noted that the beneficial influence of maternal knowledge or formal education on child growth is understood to be dependent on a minimum level of access to resources (39,(50)(51)(52)(53). Nonetheless, our findings support the growing interest in increasing maternal educational attainment as a potential intervention toward improving child health outcomes (18,(54)(55)(56).…”
Section: Discussionmentioning
confidence: 92%
“…Effective utilisation of knowledge and skills gained from health and nutrition education is expected to improve the health and nutritional status of children through improved knowledge and care practices. However, some studies have reported that maternal nutritional knowledge is positively associated with the nutritional status of children ( 37 39 ) .…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies showed that the importance of household wealth for child nutrition and health varies according to maternal education (12)(13)(14)(15). For instance, in Benin, the positive effect of wealth on child nutritional status was larger in households with a more educated mother (15).…”
Section: Introductionmentioning
confidence: 97%